Asymmetry of the Structural Brain Connectome in Healthy Older Adults - Bonilha, Leonardo; Nesland, Travis; Rorden, Chris; Fridriksson, Julius (Frontiers in Psychiatry, 2014)
Background: It is now possible to map neural connections in vivo across the whole brain (i.e., the brain connectome). This is a promising development in neuroscience since many health and disease processes are believed to arise from the architecture of neural networks. Objective: To describe the normal range of hemispheric asymmetry in structural connectivity in healthy older adults. Methods: We obtained high-resolution structural magnetic resonance images (MRI) from 17 healthy older adults. For each subject, the brain connectome was reconstructed by parcelating the probabilistic map of gray matter into anatomically defined regions of interested (ROIs). White matter fiber tractography was reconstructed from diffusion tensor imaging and streamlines connecting gray matter ROIs were computed. Asymmetry indices were calculated regarding ROI connectivity (representing the sum of connectivity weight of each cortical ROI) and for regional white matter links. All asymmetry measures were compared to a normal distribution with mean=0 through one sample t-tests. Results: Leftward cortical ROI asymmetry was observed in medial temporal, dorsolateral frontal and occipital regions. Rightward cortical ROI asymmetry was observed in middle temporal and orbito-frontal regions. Link-wise asymmetry revealed stronger connections in the left hemisphere between the medial temporal, anterior and posterior peri-Sylvian and occipito-temporal regions. Rightward link asymmetry was observed in lateral temporal, parietal and dorsolateral frontal connections. Conclusions: We postulate that asymmetry of specific connections may be related to functional hemispheric organization. This study may provide reference for future studies evaluating the architecture of the connectome in health and disease processes in senior individuals.